REVIEW PAPER Pulmonary hypoplasia and congenital renal anomalies - May, Caroline; Greenough, Anne (Archives of Medical Science, 2006)
The association of pulmonary hypoplasia with bilateral renal agenesis is well recognised. It is important, however, for clinicians to be aware that pulmonary hypoplasia does occur with other congenital renal anomalies and worsens the prognosis. The aims of this review are to highlight other kidney and associated pulmonary abnormalities, describe the mechanisms of abnormal lung growth associated with renal anomalies and to discuss the relative merits of antenatal diagnostic and possible therapeutic interventions. Pulmonary hypoplasia most commonly occurs in fetuses with bladder outlet obstruction, but also in those with bilateral renal dysplasia/hypoplasia and multicystic kidneys. Possible mechanisms include reduced amniotic fluid volume and renal proline production and thoracic compression. Antenatally, pulmonary hypoplasia may be predicted by oligohydramnios or the presence of ex-renal compression abnormalities. Assessment of the thoracic or lung size by two-dimensional ultrasound examination is insufficiently specific, but calculation of the thoracic to head ratio may prove a more accurate method of diagnosis of fatal pulmonary hypoplasia. Magnetic resonance imaging evaluation of fetal lung volume is expensive and has limited patient acceptability; three-dimensional ultrasonography may prove a better option, but ultrasonography can be inaccurate if there is oligohydramnios. Antenatal therapeutic intervention is directed at relieving urinary tract obstruction, but vesico-amniotic shunting has a high morbidity and whether it improves the pulmonary outcome of fetuses with renal anomalies requires quantitative evaluation. It is essential if appropriate counselling is to be undertaken, to determine if a fetus with renal anomalies has associated pulmonary maldevelopment.